Wildlife Conservation and Various Reproductive Strategies, A Focus on Mice Population - Habib, Ansar; Anwar, Shahbaz; Memon, Shakeel Ahmed; Ahmed, Umair; Qousain, Syed Muhammad Zukhruf; Bilal, Muhammad; Khan, Touheed; Sani, Imran Ali; Younis, Sadia; Abdullah, Obaid Muhammad (Indus Journal of Bioscience Research, 2025)
This review explores how disturbances (wildfire, urbanization) affecting rodent populations illustrate key ecological restoration, public health, and wildlife management aspects. Understanding rodent behavior in these novel post-fire ecosystems is critical as they play a key role in recovery processes (especially vegetation recovery, seed dispersal, and trophic interactions). Despite being able to adapt to changing environments rapidly, significant gaps remain in understanding how long-term responses to environmental changes are constrained. This review aims to provide an overview of current data on rodent population dynamics and behavior, their ecological consequences following a wildfire, and the role of urban rodents as potential disease vectors. Spanning the fields of reproductive biology, population genetics, ecology, and evolution, our review highlights key drivers, including fire severity, mating system interactions, and environmental effects on rodent behavioral and fitness responses. It also assesses the limited research barriers per ecological roles of rodents as prey and seed dispersers in degraded ecosystems. These results highlight the importance of further investigation of the longer-term effects of fires on rodent populations and rodent–human interactions (e.g., zoonotic disease transmission) in urban settings. Each statement discusses whether we are taking enough cues from ecology in managing wildlife in ways that may lead to effective rodent pest control. Rodent population dynamics in post-fire and urban spaces impact ecological restoration and public health. They influence vegetation, seed dispersal, and food webs but remain understudied in fire-affected habitats. Their role in zoonotic disease transmission makes control essential. Integrated management strategies are needed to balance ecological conservation, disease mitigation, and effective rodent population control.